Estrategias de talento humano para mejorar el desempeño laboral en el GAD municipal del cantón Samborondón - Arias Briones, Cynthia Paulette (2022)
In the Municipal GAD of Cantón Samborondón, employees do not feel motivated in their workplaces, they do not work as a team, which means that they do not give good attention to the information they have to transmit to users, there are employees who do not have the profile for the position they occupy within the Institution, among other problems. The management of human talent for some time has become one of the most important areas within any organization, for a number of situations such as the inclusion of people with capacities, knowledge, skills, values, that help to improve the organization's objectives effectively and efficiently......